(untitled) (Research, Society and Development, 2021)
Tooth eruption is one of the manifest as part of the child’s growth and development. Several factors can be related to the moment of eruption of permanent teeth resulting from multiple causes that vary from genetic, environmental, ethnic and racial orders. The objective of this research was to verify if there is an association of the child’s weight with eruption of the first permanent molar. The research analyzed 224 children residing in the Santos region of the State of São Paulo aged between 5 and 7 years. The clinical examination was performed in the dental chair, the presence of an erupted molar was considered to be any part of the crown that ruptured the gingiva and was visible in the oral cavity and in any quadrant. After the exam, the children were heavy barefoot and without a T-shirt. This results showed that the weight did not include an influence on the tooth eruption, and that in the group studied, female children had earlier eruption than boys.